Revitalization without needles: post radiation therapy scars in oncology patients - Ribé Subirà, Natalia (Aesthetic Medicine, 2025)
Background: High-quality non-invasive treatments, when performed by experienced professionals, can be highly beneficial for cancer patients seeking to restore the appearance and health of their skin after aggressive therapies such as chemotherapy and radiotherapy. In this report, we present a clinical case involving needle-free revitalization using a specialized protocol targeting radiation-induced scars, yielding excellent outcomes. Methods: We describe the case of a 44-year-old female oncology patient presenting with erythema and skin lesions on her arms, caused by compulsive scratching due to post-radiation pruritus. The patient underwent a combination of needle-free biostimulation (PRX-T33) and FDA-approved non-invasive microneedling (SKIN PEN). PRX-T33, a formulation containing 33% trichloroacetic acid and hydrogen peroxide, was used to stimulate dermal regeneration without causing frosting, leading to enhanced skin quality and reduction of post-treatment marks. The addition of non-invasive microneedling further promoted skin regeneration and collagen stimulation, effectively addressing acneiform scars and similar imperfections. This synergistic approach led to skin rejuvenation, regeneration, and an overall improvement in skin tone. Results: The treatment resulted in visible enhancement of skin tone and a reduction of post-aggression marks on both arms. These improvements confirmed the appropriateness of the combined therapeutic approach. Additionally, the patient expressed high satisfaction with the outcomes, further supporting the efficacy of the treatment. Conclusion: The combination of needle-free biostimulation (PRX-T33) with non-invasive microneedling (SKIN PEN) represents an effective and safe option for improving skin quality in oncology patients. The absence of adverse events highlights its suitability for this particularly sensitive patient group.